The Importance of Innovation in Creating New Products and Services and Strategies to Encourage Creativity Among Entrepreneurs - Nurmala, Lia; Bakhtiar, Marfuatul Jannah; Kamaruddin, Syamsu A. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Innovation and creativity have a crucial role in entrepreneurship to achieve competitive advantage. This article discusses the concept of innovation in product and service development, as well as strategies for encouraging creativity in entrepreneurship. Innovation includes updating methods and technology that can add economic and social value, while creativity is considered the skill of creating new ideas. With a qualitative approach based on literature review, this research summarizes the importance of model adoption Diffusion of Innovations which includes stages from knowledge to confirmation, as a guide for entrepreneurs in understanding the process of accepting and implementing innovation. Research shows that internal factors, such as an organizational culture that supports creativity, as well as external factors, such as developments in digital technology, can encourage innovation. Social media plays an important role in increasing consumer engagement and strengthening brands. Strategies to increase creativity include training, incentives, collaboration, as well as the use of technology and ongoing evaluation. It was concluded that a work environment that supports freedom of thought and exploration, together with these strategies, can increase creativity and innovation in a sustainable manner. The recommendations provided include creating a collaborative work environment, innovative skills training, adopting data-based technology, and utilizing social media for marketing.